Estudo sobre os benefícios obtidos pelos brasileiros em Portugal através de uma análise do fluxo migratório - Pinto, Morgana Ribeiro (My University, 2019)
The flow of migration is something that can be seen even before the globalization is known by its name. But knowing about the causes and reasons that led an individual to seek for migration is something that has been current. The purpose of this study is to understand the migratory flow of Brazilians to Portugal, seeking to identify the benefits that Portuguese almost-nationality can offer to Brazilian migrants. The motivation varies from economic, political, social and personal effect from each one. Brazilians have benefits that facilitate the and stay in Portugal, a country in Europe that has great chances of studying and such advantages that are not disclosed and that many Brazilians do not know. Knowing about the Statute of Equality, for example, contributes to the Brazilians who want to study abroad, work abroad, try something new and challenging. They also have the facility of remaining stable in another country, other than the one they are from. Therefore, the theoretical basis of the subjects have been studied, and soon after conducting a qualitative research with 6 Brazilians, four of them being still resident of Portugal and 2 who have returned to Brazil. The results showed that the Brazilian who participated in the research were looking for a better quality of life, but also showed that the benefits that are offered by treaties between Brazil and Portugal are not much publicized (sic).
O fluxo de migração é algo visto antes da globalização ser conhecida por esse nome. Mas saber sobre as causas e os motivos que levaram um indivíduo procurar a migração é algo sempre atual. O objetivo desse trabalho é entender o fluxo migratório de brasileiros para Portugal, procurando identificar os benefícios que a quase-nacionalidade portuguesa pode oferecer para os migrantes brasileiros. A motivação varia de situações econômicas, políticas, sociais e pessoais. Os brasileiros possuem benefícios que facilitam a ida e estadia em Portugal, um país da Europa que tem grandes chances de estudo e emprego, tais vantagens que não são divulgadas e que muitos brasileiros não conhecem. Para tanto, estudou-se a fundamentação teórica dos assuntos abordados e foi realizado uma pesquisa qualitativa com seis brasileiros, sendo quatro deles que ainda residem em Portugal e dois que retornaram para o Brasil. Os resultados mostraram que, de modo geral, os brasileiros foram em busca de uma melhor qualidade de vida, mas também mostrou que os benefícios que são oferecidos por meio dos tratados entre Brasil e Portugal são pouco divulgados (sic).
Keywords: Migração; Tratados